THE INFLUENCES OF TASK-TECHNOLOGY FIT, UTILIZATION, AND USER SATISFACTION TOWARDS EMPLOYEE PERFORMANCE IN USING ACCOUNTING INFORMATION SYSTEM (Study on the Employee of Small and Medium Industries in Malang) - Sutantyo, Fariz Achmad (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
This study is aimed to provide evidence related to the influences of Task Technology Fit (TTF), utilization, and user satisfaction towards employee performance in using Accounting Information System (AIS) in Small and Medium Industries (SMIs) Malang. This study uses a model combining the Technology to Performance Chain (TPC) and End-User Computing Satisfaction (EUCS) to analyze the factors that may affect the implementation of AIS. This research is a quantitative research. The sample used is 40 employees of SMIs in Malang registered as an active company in Department of Industry and Commerce year of 2016/2017 obtained using nonprobability sampling. Data collection method in this research is done by conducting survey with a paper questionnaire as its instrument. This data analysis is conducted using multiple regression analysis. The result shows that task technology fit do not affect the employee performance in SMIs Malang. However, utilization, and user satisfaction positively affect the employee performance in SMIs Malang. The variable that has the most influence on employee performance of using AIS is user satisfaction.Keywords: Accounting Information System (AIS), Task technology fit, utilization, user satisfaction, employee performance